A rapid and reliable method of counting neurons and other cells in brain tissue: a comparison of flow cytometry and manual counting methods - Collins, Christine E.; Young, Nicole A.; Flaherty, David K.; Airey, David C.; Kaas, Jon H. (Frontiers in Neuroanatomy, 2010)
It is of critical importance to understand the numbers and distributions of neurons and non-neurons in the cerebral cortex because cell numbers are reduced with normal aging and by diseases of the CNS. The isotropic fractionator method provides a faster way of estimating numbers of total cells and neurons in whole brains and dissected brain parts. Several comparative studies have illustrated the accuracy and utility of the isotropic fractionator method, yet it is a relatively new methodology, and there is opportunity to adjust procedures to optimize its efficiency and minimize error. In the present study, we use 142 samples from a dissected baboon cortical hemisphere to evaluate if isotropic fractionator counts using a Neubauer counting chamber and fluorescence microscopy could be accurately reproduced using flow cytometry methods. We find greater repeatability in flow cytometry counts, and no evidence of constant or proportional bias when comparing microscopy to flow cytometry counts. We conclude that cell number estimation using a flow cytometer is more efficient and more precise than comparable counts using a Neubauer chamber on a fluorescence microscope. This method for higher throughput, precise estimation of cell numbers has the potential to rapidly advance research in post-mortem human brains and vastly improve our understanding of cortical and subcortical structures in normal, injured, aged, and diseased brains.